((x^2-3x-18)/(x+3))
((x-6)(x+3))/(x+3)
The x+3 on top cancels out the x+3 on the bottom so all you have left is
x-6
Hope I didn't mess up for your sake!
Answer:
The point which is the midpoint is equally spaced from both ends of the line. We know the coordinates of A and we know the coordinates of M, the midpoint.
Step-by-step explanation:
Answer:
A!
Step-by-step explanation:
Answer:
d. y - 3 = f(x).
Step-by-step explanation:
The red graph is the translation of the black one up 3 units.
y = f(x) becomes y = f(x) + 3 or
y - 3 = f(x).